Identification Of Local Origin Income Factors In The Tourism Sector In Buton Selatan District - Almadani, La Ode Aslam; Hamrullah, Hamrullah; Dewi, Andi Ratna Sari (Economy and Finance Enthusiastic, 2023)
Tourism has been transformed into one of the economic sectors with extraordinary potential to support the economic growth of a region. The tourism industry has a significant role in the context of a country. South Buton Regency has great potential to increase local revenue (PAD) through tourism. This potential is based on various factors that make South Buton Regency an attractive tourist destination. This study aims to identify the factors of local revenue in the tourism sector in the South Buton Regency. The research method is in the form of observation, and direct interviews with the parties involved, and then the data is analyzed using descriptive analysis of the level of conformity through the level of interest and level of satisfaction. The study results show that the village's original income factors in the tourism sector are adequate infrastructure, effective promotion and marketing, and diversification of tourism products. The level of conformity obtained from the questionnaire results on the level of importance and level of satisfaction of local revenue factors in the tourism sector in South Buton Regency shows an average value of> 100%, namely 107.95% in the very satisfied category.